Representasi Kehidupan dan Perlawanan dalam Puisi ‘Ala Hadzihi Al-Ardh Ma Yastahiqqu al-Hayah Karya Mahmoud Darwish (Kajian Semiotika Roland Barthes) - Muhammad Fachri; Akmaliyah Akmaliyah; Maman Abdul Djaliel; Setia Gumilar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
This study aims to describe how Mahmoud Darwish’s poem ‘Ala Hadzihi Al-Ardh Ma Yastahiqqu Al-Hayah represents life through poetic signs and how forms of resistance are interpreted and articulated based on Roland Barthes’ semiotic approach. This study employed a qualitative descriptive method using library research and documentation techniques. The research data consist of poetic lines containing linguistic signs, imagery, and symbols, which were analyzed at the levels of denotation, connotation, and myth. The findings reveal that the representation of life is constructed through poetic signs derived from nature, everyday life, culture, and women's experiences, portraying life as a resilient force that endures amid oppression. Meanwhile, the representation of resistance is interpreted and articulated through collective memory, hope, courage, art, and love for the homeland as expressions of preserving identity and humanity. At the level of myth, the poem constructs a discourse in which life and resistance are inseparable elements in sustaining the identity and existence of the Palestinian people. The findings further indicate that Darwish’s poem represents Palestine not merely as a contested geographical territory but also as a humanitarian space that continues to exist through the representations of life and resistance, while simultaneously conveying an ideology of resilience and the struggle against oppression.